2022
DOI: 10.2351/7.0000773
|View full text |Cite
|
Sign up to set email alerts
|

Toward defect-free components in laser metal deposition with coaxial wire feeding through closed-loop control of the melt pool temperature

Abstract: Laser metal deposition (LMD) is an additive manufacturing process in which a metal powder or wire is added to a laser-induced molten pool. This localized deposition of material is used for the manufacturing, modification, and repair of a wide range of metal components. The use of wire as feedstock offers various advantages over the use of powder in terms of the contamination of the process environment, the material utilization rate, the ease of handling, and the material price. However, to achieve a stable pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Specialized optics have been developed to shape the laser beam in a way that enables wire feeding through the center of the beam to ensure a distribution of laser radiation over the wire [121][122][123]. The coaxial approach consists of feeding the wire in the center of multiple single lasers (donut shape) or inside an annular laser beam, providing diverse options for the process [54,79,124,125].…”
Section: Coaxial Wire Feedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Specialized optics have been developed to shape the laser beam in a way that enables wire feeding through the center of the beam to ensure a distribution of laser radiation over the wire [121][122][123]. The coaxial approach consists of feeding the wire in the center of multiple single lasers (donut shape) or inside an annular laser beam, providing diverse options for the process [54,79,124,125].…”
Section: Coaxial Wire Feedingmentioning
confidence: 99%
“…This complexity also contributes to higher sensitivity to height deviations with this head type [116,128]. Therefore, despite being directionally independent, its broader industrial adoption is hindered due to the processes' sensitivity to disturbances [125]. In contrast with lateral wire feeding, in coaxial wire feeding, the positive defocusing of the beam cannot result in a stable process as it leads to wire melting above the substrate, which is detrimental to the process.…”
Section: Coaxial Wire Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the hardness measurements were performed with a fully automated hardness tester (Qness 60 A + EVO, ATM Qness GmbH, Germany). The diagonal lengths of the indentations were determined manually in the software to ensure a maximal accuracy [39].…”
Section: Systemsmentioning
confidence: 99%
“…Junhui Li et al 8 deposited laser-fed powder additive manufacturing specimens without the presence of porosity by varying the amount of defocus to increase the laser spot diameter. Christian Bernauer et al 9 experimented with different processes of 316L laser fusion by varying the focal position of the laser beam to obtain a 2.75 mm diameter annular laser spot and found that the volume of the deposited weld channel increased signi cantly at higher melt pool temperatures, however, the overall hardness of the melt pool was rather lower. Yanhua Zhao et al 10 , on the other hand, argued that the variation of the defocusing amount can change the convergence and divergence of the beam, and large defocusing amount has a more uniform energy density distribution.…”
Section: Introductionmentioning
confidence: 99%